Early Sequential Microcirculation Assessment In Shocked Patients as a Predictor of Outcome: A Prospective Observational Cohort Study. Issue 5 (May 2021) - Holley, Anthony D.; Dulhunty, Joel; Udy, Andrew; Midwinter, Mark; Lukin, Bill; Stuart, Janine; Boots, Robert; Lassig-Smith, Melissa; Holley, Robert B.; Paratz, Jenny; Lipman, Jeffrey
ABSTRACT: Objectives: A dysfunctional microcirculation is universal in shock and is often dissociated from global hemodynamic parameters. Persistent microcirculatory derangements reflect ongoing tissue hypoperfusion and organ injury. The initial microcirculatory dysfunction and subsequent resolution could potentially guide therapy and predict outcomes. We evaluated the microcirculation early in a heterogenous shocked population. Microcirculatory resolution was correlated with measures of tissue perfusion and global hemodynamics. The relationship between the microcirculation over 24 h and outcome were evaluated. Design: We prospectively recruited patients with all forms of shock, based on global hemodynamics and evidence of organ hypoperfusion. Setting: A 30-bed adult intensive care unit (ICU). Patients: Eighty-two shocked patients. Measurements and Main Results: Following the diagnosis of shock, patients underwent a sublingual microcirculation examination using Sidestream Dark Field Imaging. The median age of patients was 66 years old (interquartile range [IQR] 54–71), with an Acute Physiology and Chronic Health Evaluation II of 27 (IQR 20–32). Microcirculatory parameters included Percentage Perfused Vessels (PPV), De Backer Score, and a heterogeneity index in patients with septic shock, according to the second consensus guidelines Additional parameters collected: temperature, heart rate and arterial pressure, cumulative fluid balance, and vasopressor use. Arterial blood samples were taken at the time of microcirculatory assessments, providing HCO3, lactate concentrations, PaO2, and PaCO2 measurements. A statistically significant improvement in PPV and the heterogeneity index was demonstrated. This improvement was mirrored by biomarkers of perfusion; however, the global hemodynamic parameter changes were not significantly different over the 24-h period. The early microcirculatory improvement was not predictive of an improvement in acute kidney injury, length of stay, ICU, or hospital mortality. Conclusions: Early sequential evaluation of the microcirculation in shocked patients, demonstrated statistically significant improvement in the PPV and microvascular heterogeneity with standard care. These improvements were mirrored by biomarkers of organ perfusion; however, the changes in global hemodynamics were not as pronounced in this early phase. Early improvement in the microcirculation did not predict clinical outcome. Abstract : Supplemental Digital Content is available in the text